Results of Previous Discectomy and Implantation of Peek Intervertebral Keys for Cervical Interdiscular Hernia (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Intervertebral disc herniation is one of the most pressing problems in neurosurgery, traumatology, and neurorehabilitation, due to long-term spinal cord injury, severe functional impairments associated with patients' ability to self-care, control limb and pelvic functions, a high level of disability, and numerous complications associated with the complexity of patients' socio-psychological adaptation.Herniated discs and spinal cord compression account for 15–30–42% of all spinal diseases [1, 13]. In large industrial cities of Russia (St. Petersburg, Nizhny Novgorod, Irkutsk), the incidence of herniated discs and spinal cord compression is 5.58–7.6 cases per 10,000 population [5, 7, 10], in Kazakhstan – 4.3 cases [1], and in Ukraine – 6.4 cases [13]. According to Murphy KP [14], the incidence of herniated discs and remote spinal cord injuries in the USA is 0.2–0.5 cases per 10,000 population. In Russia, the number of cases of herniated discs and spinal cord compression increases by 8,000 annually. In the USA, 10,000 new cases of herniated discs and spinal cord compression are registered annually [2, 14].Cervical osteochondrosis is the second most common disorder after lumbar osteochondrosis and most often occurs in working-age patients aged 25–60. The danger of cervical disc herniation is associated with a high risk of developing myelopathy, which leads to serious neurological disorders, decreased quality of life, and disability.Aim: Analysis of the results of surgical treatment of the cervical spine using anterior   decompression and the intercorporeal cage stabilization developed by us.